Coderivatives of implicit multifunctions and stability of variational systems - Qui, Nguyen Thanh (Journal of global optimization, 2016)
We establish formulas for computing/estimating the regular and Mordukhovich coderivatives of implicit multifunctions defined by generalized equations in Asplund spaces. These formulas are applied to obtain conditions for solution stability of parametric variational systems over perturbed smooth-boundary constraint sets.